Constrained Rational Cubic Spline and Its Application (Journal of Computational Mathematics, 2001)
In this paper, a kind of rational cubic interpolation function with linear denominator is constructed. The constrained interpolation with constraint on shape of the interpolating curves and on the second-order derivative of the interpolating function is studied by using this interpolation, and as the consequent result, the convex interpolation conditions have been derived.